Solid-phase synthesis and preliminary evaluation of 1,6,8-trisubstituted tetrahydro-2H-pyrazino [1,2-a] pyrimidine-4,7-diones as a NF-kB inhibitor - Kim, Jin-Woong; Cho, Jung-Hyuck; Han, Taehee; Lee, JongBaek; Oh, Chang-Hyun (WILEY-V C H VERLAG GMBH, 2006)
The solid-phase synthesis of new series of 1,6,8-trisubstituted tetrahydro-2H-pyrazino[1,2-alpha]pyrimidine-4,7-diones as bicyclic beta-turn mimetics is described. Their NF-kB inhibition activities were tested and the effect of substituents on bicyclic ring was investigated. Among the prepared compounds, the fluorobenzyl and methoxybenzyl group Substituted compounds 26 and 27 at C-1 and C-8 position showed more inhibitory activities than the others. Tested at a concentration of 10 uM, these two compounds showed a 60% inhibition against the target NF kB 549.
Keywords: KAPPA-B; CONFORMATIONAL-ANALYSIS; MAJOR CULPRIT; MIMETICS; RECEPTOR; CANCER; INFLAMMATION; ACTIVATION; SCAFFOLDS; DESIGN